The Influence of Self-Efficacy on the Understanding of Science Concepts in Elementary Schools: A Meta-Regression Analysis - Suci Nurhayati; Afra Munifah; Olivia Amelizky (CV. Akademi Merdeka, 2026)
This research aims to determine the extent to which self-efficacy affects students' understanding of science concepts, specifically in terms of translation, interpretation, and extrapolation abilities. These aspects reflect students’ cognitive skills in explaining, interpreting, and predicting scientific phenomena. The research design used is a quantitative approach with a survey method and non-experimental design. The sample of this study amounted to 50 students, consisting of 22 girls and 27 boys from five elementary schools that are part of Gugus 1 in Pasawahan District, selected through purposive sampling technique. Data collection techniques were carried out using tests in the form of test items measuring science concept understanding and non-tests in the form of questionnaires to measure student self-efficacy. Data were analyzed using simple linear regression to test the relationship between self-efficacy and understanding of science concepts. The results showed that there was a significant relationship between self-efficacy and understanding of science concepts, with a Pearson correlation of 0.341 (p<0.05). This finding indicates that students with a high level of self-efficacy have a better understanding of science concepts. The contribution of this research is to strengthen the understanding of the importance of self-efficacy in science learning. This research is also significant for the development of learning methods that can increase students' self-efficacy to improve understanding of science concepts in the future.